2021
DOI: 10.1002/mds.28478
|View full text |Cite
|
Sign up to set email alerts
|

Development of SARAhome, a New Video‐Based Tool for the Assessment of Ataxia at Home

Abstract: Background: Clinical scales such as the Scale for the Assessment and Rating of Ataxia (SARA) cannot be used to study ataxia at home or to assess daily fluctuations. The objective of the current study was to develop a video-based instrument, SAR-A home , for measuring ataxia severity easily and independently at home. Methods: Based on feasibility of self-application, we selected 5 SARA items (gait, stance, speech, nosefinger test, fast alternating hand movements) for SAR-A home (range, 0-28). We compared SARA h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 9 publications
1
33
0
Order By: Relevance
“…Future studies should investigate correlations between patient-reported quality of life and gait measures discriminating gait characteristics from SCA from HC. Fourth, given a considerable degree of intraindividual variability in SARA score at home, 56 future studies should explore the potential of gait variability measures to capture daily fluctuations in a free-living condition. Finally, we ranked mobility measures characterizing mobility impairments in SCA and prodromal SCA based on AUC.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should investigate correlations between patient-reported quality of life and gait measures discriminating gait characteristics from SCA from HC. Fourth, given a considerable degree of intraindividual variability in SARA score at home, 56 future studies should explore the potential of gait variability measures to capture daily fluctuations in a free-living condition. Finally, we ranked mobility measures characterizing mobility impairments in SCA and prodromal SCA based on AUC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a video‐based assessment of the SARA has been developed, 18 indicating the need for measures that are able to be performed remotely. The SARA home enables items of the SARA to be performed independently by participants at home.…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine evaluations of common scales used in movement disorders have been found to be non-inferior to in-person evaluations [6]. One recent prospective study was able to validate a modified Scale for the Assessment and Rating of Ataxia (SARA) self-recorded by ataxia patients in their own homes [9]. They found that the concordance rate between SARA scores performed in person highly correlated with SARA scores obtained on home videos and evaluated by a trained examiner (r = 0.985, p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%